Beyond Doubt: The Case Against 'Not Proven'. Issue 4 (1st December 2021) - Chalmers, James; Leverick, Fiona; Munro, Vanessa E.
Abstract: Scotland, unusually, has three verdicts in criminal trials: guilty, not guilty, and not proven. The not proven verdict, regarded by many as an intermediate option between the other two, has been the subject of a long‐running debate as to whether it should be abolished. In this article we argue that it should. Drawing on empirical evidence from two recent studies, we cast doubt on the arguments most often made in its favour – that it serves a valuable communicative function, protects against wrongful conviction, and/or increases juror satisfaction. There is no consensus on its meaning or appropriate application in any given case, and it risks both stigmatising an acquitted accused and diminishing complainers' opportunities for closure. It is doubtful that it prevents wrongful conviction, but even if it does, there are more effective measures in this regard.